Periodontitis and identification of undiagnosed hyperglycemia - Larissa Oliveira MATOS; Ariely Barbosa FREITAS; Cleverton Correa RABELO; Ana Emília Farias PONTES; Fernanda Oliveira Bello CORREA (Universidade Estadual Paulista, 2021)
Abstract Introduction Individuals with pre-diabetes have altered glycemic levels, are generally asymptomatic, and are at increased risk for developing type 2 diabetes mellitus. Objective Identify the prevalence of periodontal individuals with undiagnosed hyperglycemia and associated impact factors. Material and method Fifty-six patients with periodontitis and without diabetes self-report, users of dental clinic services at Federal University of Juiz de Fora were included in this research, during one year and a half of experimental evaluation. Socioeconomic and demographic data, anthropometric patterns, fasting capillary blood glucose, and complete periodontal examination (six sites per tooth) were evaluated. Result The sample consisted of 58.9% female, mean age 53 years old, 58.9% obese/overweight and 45.3% had a low level of education. A total of 28.6% (n=16) participants had undiagnosed hyperglycemia (between 100 to 160 mm / dL), of which 81.3% were obese/overweight, 25% were smokers, 56.3% reported having a history of diabetes in the family, 93.8% had a family income up to 2 brazilian´s minimum wages. BMI values were higher in the group of patients with hyperglycemia (29.8 ± 5.7, p = 0.03) compared to the group without hyperglycemia (26.6 ± 5.6). Patients with hyperglycemia had a greater number of sites with clinical attachment loss (CAL) between 4 and 6 mm (p = 0.04) when compared with the normoglycemic group. Conclusion Undiagnosed CAL attachment loss between 4 and 6 mm due to periodontitis than normoglycemic individuals.